Astrology as Heresy in Contemporary Belief. (15th February 2019) - Phillipson, Garry
Abstract : Astrology has been characterised as a heresy by many Christian thinkers, from the time of the early Church Fathers to the present day. In contemporary discourse, astrology is often treated as if it were a heresy against science. I provide examples of astrologers being treated as heretics in the name of science, and an alternative conception of astrology as a form of divination, not dependent on scientiﬁc substantiation. I argue that the 'astrology' often criticised in the name of science may be deﬁned as much by scientism's need for a construction to deﬁne itself against, as by the actual views of horoscopic astrologers. The emerging picture is that criticisms of astrology are typically based on a mixture of legitimate objections and scientistic belief. I conclude that scientism's unspoken aspiration to orthodoxy emerges through the parallels between its approach to astrology and that of the Church.